Tauhid Sebagai Fondasi Epistemologis: Tafsir Tarbawi Atas Q.S. Al-Baqarah [2]:163 Bagi Paradigma Pendidikan Islam - Helmy, Helmy Abdullah; Surahman, Cucu; Sumarna, Elan (NALAR, 2025)
Contemporary Islamic education faces an epistemological crisis marked by the dichotomy between religious and non-religious sciences due to the adoption of a secular paradigm that separates the value of tawhid from the learning process, resulting in fragmented knowledge and the loss of balance in the hierarchy of knowledge (loss of adab). This study aims to analyze Q.S. al-Baqarah [2]:163 using a tafsir tarbawi approach to identify the core principles of tawhid and their implications for the epistemological foundations of Islamic education, as well as to construct a tawhid-based conceptual framework as an alternative paradigm to overcome the knowledge–religion dichotomy. Using a library research design and a tafsir tarbawi methodology that integrates linguistic-grammatical, contextual (munasabah al-ayat), and comparative-critical analysis of classical and contemporary commentaries, the study identifies five central principles of tawhid: (1) tawhid al-ma‘rifah (unity of the source of truth), (2) kulliyyat al-rahmah (universality of divine mercy), (3) nafy al-shirk (negation of partners to God), (4) takamul al-‘ubudiyyah wa al-khilafah (integration of vertical and horizontal dimensions), and (5) ta‘yin al-huwiyah al-ma‘rifiyyah (formation of epistemic identity). These principles generate ontological implications (a theocentric-anthropocentric conception of the human and fitrah), epistemological implications (integration of revelation, reason, and empirical inquiry, alongside a methodology resistant to secularization), and axiological implications (mercy, justice, integrity, and social-ecological responsibility). Q.S. al-Baqarah [2]:163 thus provides a theological-epistemological foundation for an Islamic education paradigm that integrates spiritual, intellectual, and moral dimensions, whose implementation requires curriculum reconstruction that harmonizes diverse disciplines within a tawhidic framework and the development of holistic assessment systems that measure cognitive, moral, and spiritual domains in an integrated manner.